Novel Analytical Approach of Quantitative Spectrophotometry Intended for Quantitation of Absorbance Quenching Analyte Through Measurement of the Absorbing System's Permittance - Rangnath Labhade, Shivaji; Bhaskar Gakwad, Vishwas (Asian Journal of Chemistry, 2010)
This paper proposed a new analytical method for quantitative spectrophotometry. In this study, the analyte's absorbance quenching capability towards the specific light absorbing system was utilized for quantitation of the analyte by measuring the system's transmittance. The absorbing system used was acidic 0.001 M KMnO4 solution and the analytes quantitatively determined at 550 nm were nitrite, thiourea, hydroquinone, thiocyanate and tin(II). Contrary to Beer's law, it was found that for parallel monochromatic radiation that passes through a solution of an absorbing system of constant path length and concentration, the radiant power of transmitted beam increases exponentially as the concentration of absorbance quenching analyte increases arithmetically. The chemical reaction of an analyte with the absorbing system quenches the absorbance, resulting in the increase in the system's transparency which is termed in this paper as clearance, a termed designating the ratio of transmittance of test solution (absorbing system plus analyte) to transmittance of reagent blank solution (absorbing system only), measured at fixed wavelength in a cell of constant path length. The clearance of an absorbing system increases exponentially with arithmetic increase in the concentration of the analyte. The logarithm of clearance termed as permittance in this paper, is plotted versus the concentration of analyte for construction of the calibration curve. Though the suggested method employs techniques contrary to Beer's law, yet the efficacy and validity of the method has been demonstrated logically, mathematically and experimentally.